In-Silico Evaluation of 4-(2,4-difluorophenyl)-2-(2-(3-(trifluoromethyl)benzylidene)hydrazinyl)thiazole - Yilmaz, Engin; Cukurovali, Alaaddin (Springer/Plenum Publishers, 2025)
In this study, 4-(2,4-difluorophenyl)-2-(2-(3-(trifluoromethyl)benzylidene)hydrazinyl)thiazole (FBHT) was synthesized and characterized with IR, 1H NMR, 13C NMR and 19F NMR spectroscopic methods. FBHT was optimized using Gaussian 09 software. Fukui parameters of FBHT were calculated using atomic charges obtained from the optimization file calculated from Gaussian 09 program. 6RKB file downloaded from the protein databank site was used for biological activity. 6RKB file is the crystal structure of human monoamine oxidase. Binding sites between FBHT and 6RKB were identified using the PyRx software. Molecular dynamics calculations were performed to determine the stapyrbility of the binding between FBHT and 6RKB. The gromacs 2025 package program was used in molecular dynamics calculations. SwissADME server was used for theoretical ADMET calculations. The binding energy of FBHT to 6RKB was calculated as -11 kcal/mol by molecular docking. According to the RMSD, H bond parameters, it was theoretically shown that FBHT can show activity on MAO-B.
Keywords: Hydrazone; ADMEt; MAO-B; Molecular dynamics calculations